Two-stage cultivation of microalga for sustainable biofuel production - Gyanendra Tripathi; Priyanka Dubey; Khwaja Osama; Suahil Ahmad; Irum; Veer Singh; Alvina Farooqui; Emanuel Vamanu; Sachchida Nand Rai; Vishal Mishra (Green Chemistry Letters and Reviews)
This two-stage system comprises an airlift-driven low-tubular photobioreactor for continuous microalgal (strain Scenedesmus sp. GTAF_01 IU) growth and an open raceway pond for stress-induced coordinated lipid accumulation due to nutrient deprivation. A support vector regression (SVR) model was used to develop the predictive model to predict the cell biomass on a dry basis at different culture conditions. A maximum biomass (dry weight) of 1.65 g was achieved at a light intensity of 27 µmol m−2 s−1 photosynthetic photon flux density (PPFD), mixing speed of 150 revolutions per minute, pH 7, and light and dark cycle of 12 h each. The model accuracy was verified by performing experiments at the optimal conditions that resulted in an enhanced biomass (dry weight) of 1.69 g, which was close to the expected one. The results also showed a significant increase in carbohydrate, protein, and lipid content of 27%, 64%, and 47%, respectively. This study provides novel insights into a two-phase cultivation system combining a closed photobioreactor and an open raceway pond for Scenedesmus sp. GTAF_01 IU, resulting in enhanced biomass growth and lipid content. This enhancement supports its potential for sustainable biofuel production within a circular economy framework.